Gender Undone: Confronting Bias in the Nuclear Field - Sneha Nair; Christina McAllister; Annina Pluff; Katherine C. Mack (International Journal of Nuclear Security, 2023)
In the face of evolving security needs, diversity is critical in nonproliferation, nuclear security, and other related fields. Despite multiple studies highlighting the need for gender balance and diversity in the nuclear nonproliferation and security space and targeted recruitment and capacity-building efforts by the International Atomic Energy Agency and states, gains in the representation of women (as well as historically underrepresented groups) have been set back by the gendered effects of the COVID-19 pandemic and slow cultural change at nuclear facilities and organizations. This issue is in large part due to the inability of initiatives aimed at diversity, equity, inclusion, and accessibility (DEIA) to deal with the structural biases of who belongsin nuclear security. Accordingly, this paper will address potential solutions and good practices for reforming organizational nuclear security culture in the United States. Integrating policies to actively confront and undo structural biases and gendered assumptions about women in nuclear security is the start of building DEIA into the broader nuclear industry and its associated organizations. Although bias is an inevitable symptom of the human condition, employers in the nuclear field can work to check biases by integrating DEIA values and assumptions that deal with gender representation into the organizational culture. This paper finds that significantly more transparency and public data reporting is needed in the sector to understand the scope of the challenge and posits the creation of a DEIA nuclear security organizational culture more reflective of DEIA values to strengthen nuclear security and improve the diversity of the nuclear field in the long term.
Keywords: nuclear security; women; gender; bias; DEI; DEIA; diversity; equity; inclusion; accessibility; nonproliferation